2016
DOI: 10.1038/srep34534
|View full text |Cite
|
Sign up to set email alerts
|

Mode of renal replacement therapy determines endotoxemia and neutrophil dysfunction in chronic kidney disease

Abstract: Bacterial infection and sepsis are common complications of chronic kidney disease (CKD). A vicious cycle of increased gut permeability, endotoxemia, inadequate activation of the innate immune system and resulting innate immune dysfunction is hypothesized. We assessed endotoxemia, neutrophil function and its relation to oxidative stress, inflammation and gut permeability in patients with CKD grade 3–5 without renal replacement therapy (CKD group, n = 57), patients with CKD stage 5 undergoing haemodialysis (HD, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 64 publications
0
22
1
Order By: Relevance
“…Recently it has been shown that patients undergoing HD have a 2.4 fold higher risk of death compared to PD patients in a large propensity matched study, that could not be attributed to initial use of central venous catheters or lack of pre-dialysis care 19 . HD patients have also been shown particularly prone to endotoxemia and subsequent innate immune dysfunction and innate immune function seems to improve after kidney transplantation 20 . These findings raise the hypothesis that the gut microbiome as major contributor to bacterial translocation and inflammation might be involved in these differences.…”
Section: Introductionmentioning
confidence: 99%
“…Recently it has been shown that patients undergoing HD have a 2.4 fold higher risk of death compared to PD patients in a large propensity matched study, that could not be attributed to initial use of central venous catheters or lack of pre-dialysis care 19 . HD patients have also been shown particularly prone to endotoxemia and subsequent innate immune dysfunction and innate immune function seems to improve after kidney transplantation 20 . These findings raise the hypothesis that the gut microbiome as major contributor to bacterial translocation and inflammation might be involved in these differences.…”
Section: Introductionmentioning
confidence: 99%
“…Plasma LPS levels were measured using a reporter cell line (hkb-htlr4; Invivogen, San Diego, CA). (25) LPS results were confirmed in FFD-fed animals (data not shown), using a commercially available enzyme-linked immunosorbent assay (CEB526Ge; Cloud-Clone Corp., Katy, TX).…”
Section: Biochemical Analysesmentioning
confidence: 81%
“…Aspartate aminotransferase (AST) was measured from plasma obtained from the inferior vena cava, using a kinetic assay (TR70121; Thermo Fisher Scientific). Plasma LPS levels were measured using a reporter cell line (hkb‐htlr4; Invivogen, San Diego, CA) . LPS results were confirmed in FFD‐fed animals (data not shown), using a commercially available enzyme‐linked immunosorbent assay (CEB526Ge; Cloud‐Clone Corp., Katy, TX).…”
Section: Methodsmentioning
confidence: 99%
“…Albumin, bilirubin, hemoglobin, uric acid, creatinine, prothrombin time and CRP were measured in the routine labouratory. LPS was detected in serum with an adapted protocol using HEK‐Blue hTLR4 reporter cells (Invivogen, Toulouse, France) as published previously . All other assays were handled according to manufacturers’ instructions.…”
Section: Methodsmentioning
confidence: 99%
“…LPS was detected in serum with an adapted protocol using HEK-Blue hTLR4 reporter cells (Invivogen, Toulouse, France) as published previously. 38 All other assays were handled according to manufacturers' instructions. Enzyme linked immunosorbent assay were used to measure calprotectin, zonulin and serum DAO (Immundiagnostic AG, Bensheim, Germany), as well as LBP and sCD14 (Hycult biotechnology, Uden, the Netherlands).…”
Section: Labouratory Measurementsmentioning
confidence: 99%